GenAI and Precarity in Canadian Software Development: A Transfeminist Intersectional Analysis of Marginalized Workers’ Experiences - Rudnicka-Lavoie, Dani (Imaginations, 2026)
This paper explores how increased use of generative artificial intelligence (GenAI) impacts workers from historically underrepresented communities in the software development industry in Canada (women, BIPOC, and LGBTQIA+). Drawing on 15 semi-structured qualitative interviews, I argue that existing labour inequalities are exacerbated by GenAI automation. By employing a critical transfeminist intersectional framework to this exploratory study, I centre the accounts of these marginalized workers in the discussion of increased automation in digital labour. This study finds that the overall devaluation of tech labour disrupts efforts at equity, diversity, and inclusion and exacerbates precarity in an increasingly precarious neoliberal job market.